WOMEN AND THE SHADOW OF BEAUTY MYTHS IN ADVERTISING - Rachmayanti, Annissah; Narwastu, Devrisca; Nagari, Avanty Damar (Lentera : Journal of Gender and Children Studies, 2024)
Over the last few years, advertising is constantly changing and continues, it’s easy to access because they can be published in various media such as print, electronic, and new internet-based media such as Youtube. Advertisements often put images of gender and human figures, both women and men. In Indonesia, women and beauty standards are mythified in graceful, traditional way, and live according to what society has constructed. Media has involved in shaping the definition of beauty and expectation for women in a wide audiences. Beauty industries has take advantages of this, by creating beauty expectation to offer women to gain profit. This research wants to reveal women’s representation which seen in the Vaseline “Stepout” advertisement. Researchers uses a qualitative methods using John Fiske’s semiotic analysis, namely interpreting an audio-visual advertisement by looking at reality, representation, and ideology. The results of this study explain that the Vaseline “Stepout” advertisement gives women of courage to-get-out from the myths of beauty standards that have been constructed by media. Researchers also see the myths of beauty is interpreted by the word-itself, coupled with the construction of cultural hope which limit women’s movements to achieve their dreams. Keyword : Myth; Construction of beauty; Media and Gender.